Corrections to "Spatially Aware Fusion in 3D Convolutional Autoencoders for Video Anomaly Detection" - Niaz, Asim; Ul Amin, Sareer; Soomro, Shafiullah; Zia, Hamza; Choi, Kwang Nam (IEEE access, 2024)
Presents corrections to the paper, (Corrections to "Spatially Aware Fusion in 3D Convolutional Autoencoders for Video Anomaly Detection").